Analisis dan Perancangan Sistem Informasi Manajemen Pendidikan Praktik Pengalaman Lapangan (Studi Kasus : Jurusan Sistem Informasi Program Studi Pendidikan Teknologi Informasi) - Azkia Samara Devi; Satrio Agung Wicaksono; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Field experience Practice (PPL) is a course that must be pursued by students of S1 information Technology Education (PTI) Universitas Brawijaya. Based on the results of the interview with PTI's head of study program, there are several obstacles related to PPL registration process. The problem in the current PPL registration process is judged not to be sufficiently efficient and effective during implementation. This raises the loss on various parties involved, one of which is a student, a teacher of PPL and academic Prodi PTI. Based on the problems that exist today, built a design information System education management practice field experience (SIPPL) based website. In the process of designing the system used SDLC with Rational Unified Process (RUP) model. The design process was conducted using the OOAD approach and UML design modeling. The design results that have been built will be evaluated using Consistency Analysis, Traceability Matrix, and System Requirement Checklist. The result of the Consistency Analysis evaluation shows the assessment results with a percentage of 100% which means proving that the design was built and all elements of the needs of the four frameworks have been consistent. The result of traceability matrix also shows that all the needs of the business process until the end of the design can be traced to the need and can be concluded that all needs are identified. While the evaluation of the System Requirement Checklist proves that the design results that have been built have been validated all their needs by the five users and the needs are declared valid.